An amber suppressor tRNA gene derived by site-specific mutagenesis: cloning and function in mammalian cells. - Laski, F A (1982)
We describe the synthesis, cloning, expression, and in vivo function of a suppressor tRNA gene in mammalian cells. By using "primer-directed mutagenesis" on a Xenopus laevis tyrosine tRNA gene cloned into the recombinant single-strand phage M13mp5, we have generated an amber suppressor tRNA gene that has a nucleotide change--GTA leads to CTA--in the anticodon sequence. The suppressor (Su) tRNA gene was introduced into monkey kidney cells (CV-1) by using simian virus 40 (SV40) DNA as vector (SV40-tRNATyrSu+). CV-1 cells infected with virus containing the mutant, but not the wild-type, tRNA gene produce a functional amber suppressor tRNA as indicated by suppression of amber mutations in co-infecting adenovirus serotype 2-SV40 hybrids. Further evidence that suppression of these amber mutations is tRNA mediated was derived by isolation of total tRNA from CV-1 cells infected with the SV40-tRNATyr (Su+) recombinant and its use in demonstration of read through of an amber codon during in vitro translation of tobacco mosaic virus RNA in reticulocyte extracts. Interestingly, the amplification of an amber suppressor gene in CV-1 cells does not interfere with SV40 production, suggesting that suppression of amber codons may not be very deleterious to mammalian cell metabolism.